2019
DOI: 10.3390/ijms20194748
|View full text |Cite
|
Sign up to set email alerts
|

Proposed Tandem Effect of Physical Activity and Sirtuin 1 and 3 Activation in Regulating Glucose Homeostasis

Abstract: Sirtuins (SIRTs) are seven nicotinamide adenine dinucleotide (NAD+)-dependent protein deacetylases enzymes (SIRT1–7) that play an important role in maintaining cellular homeostasis. Among those, the most studied are SIRT1 and SIRT3, a nuclear SIRT and a mitochondrial SIRT, respectively, which significantly impact with an increase in mammals’ lifespan by modulating metabolic cellular processes. Particularly, when activated, both SIRT1 and 3 enhance pancreatic β-cells’ insulin release and reduce inflammation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 68 publications
1
14
0
1
Order By: Relevance
“…SIRT1 deacetylates lysine 310 of RelA/p65 subunit of NF-kB, an important subunit for for activation of transcription of proinflammatory genes, triggers inflammatory processes.This NF-kB signaling pathway is the prototypical one involved in inflammation [ 27 , 28 ]. In this way, it can be said that by affecting the secretion of this enzyme, it can help treat diabetic patients by reducing insulin resistance [ 7 , 29 ]. Janda et al showed that serum Fetuin-A levels were associated with blood sugar deposition in the arteries and that Fetuin-A had been shown to affect the AGE/RAGE pathway in the presence of inflammatory molecules [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…SIRT1 deacetylates lysine 310 of RelA/p65 subunit of NF-kB, an important subunit for for activation of transcription of proinflammatory genes, triggers inflammatory processes.This NF-kB signaling pathway is the prototypical one involved in inflammation [ 27 , 28 ]. In this way, it can be said that by affecting the secretion of this enzyme, it can help treat diabetic patients by reducing insulin resistance [ 7 , 29 ]. Janda et al showed that serum Fetuin-A levels were associated with blood sugar deposition in the arteries and that Fetuin-A had been shown to affect the AGE/RAGE pathway in the presence of inflammatory molecules [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since all the mechanisms previously described, especially Sirt1 and PPAR γ -mediated pathways, are strongly associated with inflammation and oxidative stress in metabolic diseases [ 54 ], we evaluated markers of these processes in preadipocytes after TR treatment. The reduction of TNF α , which is a proinflammatory cytokine [ 55 ], is in line with other studies demonstrating the anti-inflammatory role of TR mediated at different levels, including COX-2 expression [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The treatments were performed in the early afternoon, in 2 trials, in the fall–winter period (October–March), with the exception of 24 December–6 January. Due to the influence of antioxidant components of diet and physical activity on the level of the analysed biochemical markers [ 38 , 48 , 49 , 50 , 51 ], the subjects were asked not to change their eating or physical activity habits during the whole study period.…”
Section: Methodsmentioning
confidence: 99%